Correction to “Electroencephalographic Response of Brain Stimulation by Shock Waves From Laser Generated Carbon Nanotube Transducer” - Jooho Lee; John W. Larocco; Dong-Guk Paeng (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
In The above article [1], Fig. 5(b) is incorrectly presented as a duplicate of Fig. 5(a). The correct figure is presented here.